Cytoskeletal remodeling slows cross‐bridge cycling and ATP hydrolysis rates in airway smooth muscle. Issue 16 (18th August 2020) - Delmotte, Philippe; Han, Young‐soo; Sieck, Gary C.
Abstract: During isometric activation of airway smooth muscle (ASM), cross‐bridge cycling and ATP hydrolysis rates decline across time even though isometric force is sustained. Thus, tension cost (i.e., ATP hydrolysis rate per unit of force during activation) decreases with time. The "latch‐state" hypothesis attributes the dynamic change in cross‐bridge cycling and ATP hydrolysis rates to changes in phosphorylation of the regulatory myosin light chain (rMLC20 ). However, we previously showed that in ASM, the extent of rMLC20 phosphorylation remains unchanged during sustained isometric force. As an alternative, we hypothesized that cytoskeletal remodeling within ASM cells results in increased internal loading of contractile proteins that slows cross‐bridge cycling and ATP hydrolysis rates. To test this hypothesis, we simultaneously measured isometric force and ATP hydrolysis rate in permeabilized porcine ASM strips activated by Ca 2+ (pCa 4.0). The extent of rMLC20 phosphorylation remained unchanged during isometric activation, even though ATP hydrolysis rate (tension cost) declined with time. The effect of cytoskeletal remodeling was assessed by inhibiting actin polymerization using Cytochalasin D (Cyto‐D). In Cyto‐D treated ASM, isometric force was reduced while ATP hydrolysis rate increased compared to untreated ASM strips. These results indicate that external transmission of force, cross‐bridge cycling and ATP hydrolysis rates are affected by internal loading of contractile proteins. Abstract : An increase in internal loading of the contractile proteins resulting from actin cytoskeletal remodeling during isometric activation is associated with a decrease in cross‐bridge cycling rate and ATP hydrolysis rate.